Developing an English Textbook for Islamic Boarding School - Munir, Sirajul; Putra, Hendra; Gemilang, Febby Rizky (Journal of English Education and Teaching, 2024)
The dearth of English textbooks used as teaching resources for junior high school students at Islamic Boarding Schools (IBS) in West Sumatera, Indonesia, is the driving force behind the current study. The goal of this research is to develop an IBS English textbook. Using Sukmadinata's theory, research and development were used in this study. The phases are divided into three phases: need analysis, design, and validation. Interviews and document analysis were used to gather data. Teachers require an English textbook for instruction, according to the results of the need analysis. The textbook is meticulously created during the design phase to satisfy the demands of both teachers and students. Topics including greeting, school activities, dorm activities, sports, scout extracurricular activities, minimarket, mosque activities, and before bed are covered in the textbook along with Islamic principles and local culture. On the other hand, the activities are cheerfully and easily designed. For instance, completing crossword puzzles, matching words, and responding to simple inquiries. Additionally, the textbook made use of vibrant pictures to grab students' interest and expand their understanding. The textbook was accepted as true. The English textbook could be utilized to teach English for IBS in West Sumatera in light of these findings.